2004
DOI: 10.3989/cyv.2004.v43.i4.426
|View full text |Cite
|
Sign up to set email alerts
|

Movilidad de oxígeno en conductores iónicos A<sub>2</sub>Ti<sub>2-y</sub>Zr<sub>y</sub>O<sub>7</sub> (A: Y, Gd)

Abstract: Presentamos un estudio de la conductividad iónica en las series Y 2 Ti 2-y Zr y O 7 y Gd 2 Ti 2-y Zr y O 7 (0≤y≤2) obtenidas por síntesis mecanoquímica. Se presenta un estudio de la dinámica de iones oxígeno en estos materiales mediante la técnica de Espectroscopia de Admitancias. La variación con el contenido en Zr de la conductividad dc y de su energía de activación se interpreta en términos del aumento tanto del número de vacantes de oxígeno como del desorden en la estructura al aumentar el contenido en Zr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The two-zirconate end members, Y 2 Zr 2 O 7 and Gd 2 Zr 2 O 7 , were found to present the highest specific surface area (12.3 and 9.1 m 2 /g, respectively) of all the analyzed samples with the remaining compositions giving values within the 5-7.5 m 2 /g range. A study of the electric properties of these samples [13], have shown similar values to those obtained by other more complex processing methods.…”
Section: Gd 2 (Ti (1−y) Zr Y ) 2 Osupporting
confidence: 75%
“…The two-zirconate end members, Y 2 Zr 2 O 7 and Gd 2 Zr 2 O 7 , were found to present the highest specific surface area (12.3 and 9.1 m 2 /g, respectively) of all the analyzed samples with the remaining compositions giving values within the 5-7.5 m 2 /g range. A study of the electric properties of these samples [13], have shown similar values to those obtained by other more complex processing methods.…”
Section: Gd 2 (Ti (1−y) Zr Y ) 2 Osupporting
confidence: 75%